Farmakoterapi pada Upaya Berhenti Merokok - Diyan Ekawati; Basuni Radi; Feni Fitriani Taufik (The Indonesian Heart Association, 2015)
Nicotine dependence is a main role in tobacco dependence. Its physiological and psychological effect make smoker difficult to quit, making low success rate in smoking cessation. Combination of different method and continuity will increase smoking cessation success rate. Evidence shown that pharmacotherapy will increase success rate. Guideline’s for smoking cessation endorse physician to use first line pharmacotherapy, but it’s clinical application still limited. Physician should be aware about possibility for side effect. Some randomized controlled trial report major cardiovascular event in first line pharmacotherapy. Recent systematic review report no correlation between first line pharmacotherapy in smoking cessation and major cardiovascular event.